2018
DOI: 10.1111/petr.13253
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year longitudinal study of skeletal effects and growth in children after kidney transplantation

Abstract: This prospective study investigated growth and skeletal development for 3 years after kidney transplantation in pediatric patients, 3.4-15.0 years of age. Growth, BMD, bone resorption markers (CTX and TRACP5b), bone formation markers (PINP, ALP, and osteocalcin), PTH, and vitamin D were assessed at start, 3, 12, and 36 months after transplantation. Median GFR was 63 (range 37-96) mL/min/1.73 m after 3 years. The median height SDS increased from -1.7 to -1.1, and median BMI SDS increased from -0.1 to 0.6 over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Power calculations were made regarding total body BMC. To detect a difference of 250 g (SD 272 g) 21 with the power of 80% using the Mann–Whitney test for unpaired observations (significance level of 0.05); it was found that a sample size of 20 individuals was needed in each group. Descriptively, number and percentages were shown for categorical variables, and mean, SD, median, minimum and maximum were shown for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…Power calculations were made regarding total body BMC. To detect a difference of 250 g (SD 272 g) 21 with the power of 80% using the Mann–Whitney test for unpaired observations (significance level of 0.05); it was found that a sample size of 20 individuals was needed in each group. Descriptively, number and percentages were shown for categorical variables, and mean, SD, median, minimum and maximum were shown for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…Since height is directly proportional to absolute LBM, 75 adjusting for height is important in order to compare pediatric studies of LBM. 23,73 Ht-LBM was determined using DXA scans with the Hologic Discovery A bone densitometer, which were obtained as part of bone health surveillance. Routine bone health surveillance included DXA scan pre-transplant, at approximately 6 months and 2 years post-transplant in children >5 years of age who could tolerate the scan.…”
Section: Determination Of Ht-lbmmentioning
confidence: 99%
“…One report showed no LBM change at 12 months, 20 another showing increases after 16 months, 21 and a third showing decreases after 12 months post-transplant. 22 Studies investigating changes in LBM in pediatric kidney transplant recipients are limited [23][24][25] and small in size, but suggest accrual of LBM after transplantation. One study (n = 13) showed an increase of 27% in absolute LBM after 3 years compared to baseline, 23 while another study (n = 16) reported decreased LBM SDS scores of −0.6 SDS at 3 months compared to baseline, with a non-significant trend to improvement thereafter at 24 months post-transplant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the pediatric perspective, the CSN pediatric working group agrees with the use of vitamin D and/or calcitriol in children following kidney transplantation but would caution against the use of antiresorptives in this population given that standard steroid-tapering regimens are often sufficient for improvement in BMD in children. [129][130][131] The longterm effect of inhibiting bone reabsorption in a growing skeleton is currently not known. There are insufficient data to guide treatment recommendations in children with kidney transplants.…”
Section: Kdigomentioning
confidence: 99%